Avaliação "in vitro" da resistência adesiva ao cisalhamento na colagem de braquetes usando dois tipos de resina - Meister, Edison do Rocio (2004)
This research aims to evaluate the shear bond strenght of two resins for direct orthodontic bonding to human teeth: Concise (3M) and Ortho One (Bisco). The sample consisted in 60 caries-free premolars, which were randomly divided in two groups: group A (30 premolars with brackets bonded with Concise) and group B (30 premolars with brackets bonded with Ortho One). All teeth showed intact enamel at the vestibular surface and were extracted for orthodontic reasons, from patients aging between 11 and 16 years old. The bonding procedures were accomplished according to the manufacturer’s instructions. The specimens were submitted to shear bond strenght tests, using an occlusal-cervical load. The tests were carried out in an universal eletronic machine for mechanical assays (MTS 810), with deformation speed of 0,5 mm/min and rupture load registered in megapascal (MPa). The results obtained for group A showed a mean resistance of 29,99 + 15,89 MPa, while for the grupo B, the values demonstrated a mean resistance of 22,52 + 12,26 MPa. These results suggest that Concise orthodontic resin is more effective than Ortho One orthodontic resin when shear bond strength is considered.